Digital Calibration of Memory Errors in Passive Sigma-Delta Modulator. Issue 1 (2nd January 2020) - Moradi, Rasoul; Farshidi, Ebrahim; Soroosh, Mohamad
ABSTRACT: Based on output-referred error model of passive integrator (PI), the current study proposes a digital adaptive calibration to compensate passive delta-sigma modulator error. Due to signal attenuation in the modulator loop, the PI transfer function, which leads to gain and phase errors, causes degeneration of the modulator performance. A 1-bit pseudorandom noise test signal is applied to the input of the passive delta-sigma modulator in order to identify factors of the adaptive filter. Correlating output and test signals brings about the identification of error factors. The simulations show the effectiveness of the intrinsic error compensation of the modulator.